2004
DOI: 10.1253/circj.68.909
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Electrocardiographic Characteristics of Idiopathic Ventricular Arrhythmia Originating in the Free Wall of the Right Ventricular Outflow Tract

Abstract: adiofrequency (RF) catheter ablation is an established curative therapy for ventricular tachycardias (VT) or symptomatic premature ventricular contractions (PVCs) originating from the outflow tract (OT-VT/PVCs) in structurally normal hearts. [1][2][3][4][5][6][7][8][9][10][11][12][13] Although most of these arrhythmias have their origin in the septal aspect of the right ventricular outflow tract (RVOT), [1][2][3][4][5][6][7][8][9]14 some originate from the free wall of the RVOT. 3,4,14 However, the prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 17 publications
(36 reference statements)
2
28
0
Order By: Relevance
“…Organic heart disease was excluded by physical examination, chest radiography, and echocardiography. The 46 children (18 males, 28 females) with a mean age of 11.7± 3.4 years (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) were included in this study. Their mean body weight was 41.6±14.2 kg (17.9-71.6 kg), mean body length 147.1±18.3 cm (109.4-178.0 cm), and mean body surface area 1.30±0.30 m 2 (0.74-1.85 m 2 ).…”
Section: Editorial P 544 Methodsmentioning
confidence: 99%
“…Organic heart disease was excluded by physical examination, chest radiography, and echocardiography. The 46 children (18 males, 28 females) with a mean age of 11.7± 3.4 years (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) were included in this study. Their mean body weight was 41.6±14.2 kg (17.9-71.6 kg), mean body length 147.1±18.3 cm (109.4-178.0 cm), and mean body surface area 1.30±0.30 m 2 (0.74-1.85 m 2 ).…”
Section: Editorial P 544 Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] It is well known that some I-VTs can be eliminated by RFCA at the endocardium of the left ventricular outflow tract (LVOT) or the left sinus of Valsalva (LSV). [1][2][3]8 However, some that arise from the epicardial portion of the LVOT are remote from the LSV or left ventricular (LV) endocardium and are not amenable to ablation at those sites.…”
mentioning
confidence: 99%
“…19,20 This case-control study investigated the association between IVA and SCN5A SNPs, in which overall 11 genetic variations including 5 novel and 6 previously identified ones were detected in 31 unrelated Chinese patients with IVA and 103 healthy controls. The study showed significant difference in distribution of c.87G>A and c.1673A>G between men and women in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%